2022
DOI: 10.1007/s10971-022-06016-3
|View full text |Cite
|
Sign up to set email alerts
|

Rapid synthesis of MCM-41 and SBA-15 by microwave irradiation: promising adsorbents for CO2 adsorption

Abstract: It is known that the world scenario is one of constant search for sustainable technologies that can reduce the emission of carbon dioxide (CO2) in the atmosphere. This is because CO2 is seen as the main responsible for the increase in the generation of greenhouse gases, which leads to global warming and climate change. The development of efficient adsorbents for CO2 capture is a current challenge. MCM-41 and SBA-15 were synthesized in a microwave reactor and used as adsorbents in this work. Microwave irradiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 53 publications
1
14
0
Order By: Relevance
“…A linear trend was observed for the adsorbed amount vs. pressure (Figure 4a), which is in agreement with the literature at pressure larger or equal than 1 atm, [56][57][58] while marked curvature is observed at lower pressure, but especially at a lower temperature. [58,59] The obtained absorbed amounts are in good agreement with other reports, as summarized in Table 2.…”
Section: Resultssupporting
confidence: 91%
“…A linear trend was observed for the adsorbed amount vs. pressure (Figure 4a), which is in agreement with the literature at pressure larger or equal than 1 atm, [56][57][58] while marked curvature is observed at lower pressure, but especially at a lower temperature. [58,59] The obtained absorbed amounts are in good agreement with other reports, as summarized in Table 2.…”
Section: Resultssupporting
confidence: 91%
“…2 that the silicas exhibited a type IV(a) isotherm, sorption behavior typic of MCM-41 mesoporous materials, where the adsorption and desorption branches do not cross, which presents hysteresis of the H4 type. The presence of hysteresis H4 in the desorption branch suggests that mesopores are present, showing a sharp in ection at a relative pressure P/P0 of 0.5-0.9 [12,13] . The pore size distribution by BJH presents similar results between the two silicas, where a narrower pore distribution can be observed.…”
Section: Resultsmentioning
confidence: 99%
“…Both studies aimed to produce MCM-41, and showed similar surface areas, however demanding longer time for synthesis and removal of the surfactant. [13] It is worth mentioning that it would be possible to obtain even better textural and structural properties, since this decrease in surface area is related to the amount of surfactant still present on the silica surface, causing a blockage in the pores. This pore blockage can be associated with a decrease in micropore volume (V mp ) from 0.59 to 0.15 cm 3 g − 1 when comparing the removal of CTAB by calcination in a mu e furnace (MCM-41-M60-1) with the removal by microwave irradiation (MCM-41-OP-0.5), suggesting the presence of the surfactant in the silica micropores.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mesoporous materials have garnered significant interest for various applications, such as catalyst support, , adsorbents, , optical materials, and drug-delivery carriers , because of their unique properties, such as high surface areas, large pore volumes, high biocompatibility, and high biodegradability. Hollow mesoporous organosilica (HMOS) nanoparticles are a class of mesoporous materials with organic groups between inorganic silica frameworks in the mesoporous shell and large internal cavities. , When HMOS is used as a drug-delivery carrier, large amounts of drug molecules can be incorporated into its cavity. Therefore, considerable research has focused on various applications of HMOS.…”
Section: Introductionmentioning
confidence: 99%